(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
This article reveals the ideological and artistic features of the epic "Salvation" by the talented poetess Aydin Khodzhieva. The epic analyzes the places where the theme of independence is combined with the theme of the Motherland.